El negro es el color o ¿para qué dibujan los niños? - Marián López Fdz. Cao; Gabriela Augustowsky (Arteterapia)
This paper resumes the results of the intervention in two schools of Galician coast in Spain, soon after de oil slick in November 2003. The perception and the personal and social identity changes were analyzed as well as how the habitat conforms and transforms identity.